PZT composite film for flexible piezoelectric ultrasonic sensor and preparation method of PZT composite film
By introducing TiO2 seed layer into the PZT film to regulate its piezoelectric effect, the problem of failure of PZT/LNO/Mica flexible ultrasonic sensor in high temperature environment is solved, and the piezoelectric coefficient and sensitivity are achieved. It is suitable for complex power equipment. monitoring requirements.
Patent Information
- Application Number
- CN202411617931.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The existing PZT/LNO/Mica flexible ultrasonic sensors fail in high temperature environments and have limited sensitivity to micro ultrasonic signals, which cannot meet the application needs of complex power equipment.
By introducing TiO2 seed layer into the PZT film, the piezoelectric effect of the PZT film is regulated and its thermal stability and sensitivity are improved.
The piezoelectric coefficient d33 of the PZT film is significantly improved, the perception ability and sensitivity of the flexible piezoelectric ultrasonic sensor to ultrasonic signals is enhanced, and the reliability and effectiveness of the sensor are maintained in high temperature environments.
Smart Images

Figure CN119497561A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sensors and relates to a PZT composite film for a flexible piezoelectric ultrasonic sensor and a preparation method thereof. Background Art
[0002] Piezoelectric materials can convert tiny mechanical deformations into electrical signals, thereby realizing the conversion between force signals and electrical signals, and have received widespread attention in the fields of materials science and engineering.
[0003] Currently, the most widely used organic piezoelectric material PVDF can detect ultrasonic signals at room temperature. However, due to its organic properties, it is easy to decompose. The prepared flexible piezoelectric film sensor is not suitable for use at high temperatures and has poor temperature stability. Inorganic piezoelectric materials have been widely used in various sensing fields under higher temperature environments in recent years due to their good temperature stability. Among these piezoelectric materials, lead zirconate titanate (PZT) has been widely used in various fields including sensors, actuators, energy harvesting devices, etc. due to its outstanding piezoelectric properties. Therefore, it has attracted widespread attention in the research of piezoelectric materials in recent years. Among the various properties of PZT film, its piezoelectric properties are particularly important in its practical applications. In recent years, researchers have been constantly exploring ways to enhance the performance of PZT materials.
[0004] Compared with the traditional rigid PZT thin film sensor prepared on Pt / Si hard substrate, the PZT flexible piezoelectric ultrasonic sensor prepared on LaNiO3 / Mica substrate can achieve perfect adhesion to the surface of complex power equipment and can adapt to more complex power equipment use environment; at the same time, the flexible piezoelectric ultrasonic sensor prepared by PZT / LNO / Mica has higher sensitivity than the PZT / Pt / Si rigid piezoelectric ultrasonic sensor and is therefore widely studied.
[0005] However, the operating temperature of the flexible ultrasonic sensor made of PZT / LNO / Mica film is between 0-150 degrees Celsius. High temperature will cause internal polarization failure and film depolarization, and the sensor will be unable to sense ultrasonic signals. In addition, due to its limited piezoelectric coefficient d33 and large dielectric constant, its sensitivity to tiny ultrasonic signals is further limited. Therefore, for the application scenarios of complex power equipment, this kind of flexible ultrasonic sensor cannot meet the use conditions at all.
[0006] In view of the above reasons, it is urgent to conduct in-depth research on flexible ultrasonic sensors prepared by PZT thin films and explore a sensor with excellent temperature stability and high sensitivity. Summary of the invention
[0007] In order to overcome the above problems, the present invention proposes a PZT composite film for a flexible piezoelectric ultrasonic sensor and a preparation method thereof, and the piezoelectric effect of the PZT film is regulated by a TiO2 seed layer, so that the prepared flexible piezoelectric ultrasonic sensor exhibits excellent thermal stability and sensitivity.
[0008] Specifically, the purpose of the present invention is to provide the following aspects:
[0009] In a first aspect, a PZT composite film is provided, and the piezoelectric effect of the PZT film is regulated by a TiO2 seed layer.
[0010] Wherein, the relative dielectric constant of the PZT composite film is 200-300.
[0011] Wherein, the PZT composite film includes from top to bottom: a PZT film layer, a TiO2 seed layer and a substrate.
[0012] Wherein, the thickness of the TiO2 seed layer is 50~500nm.
[0013] Wherein, the thickness of the PZT thin film layer is 500-2000nm.
[0014] Wherein, the substrate is a polymer substrate, a metal platinum substrate or a LNO / Mica substrate.
[0015] In a second aspect, a method for preparing the PZT composite thin film according to the first aspect is provided, the method comprising:
[0016] Step 1, depositing TiO2 precursor colloid on a substrate to obtain a TiO2 precursor film;
[0017] Step 2: depositing a PZT precursor sol on the TiO2 precursor film to obtain the PZT composite film.
[0018] In step 1, the TiO2 precursor colloid is prepared by a sol-gel method.
[0019] In step 1, the thin film formed by the TiO2 precursor colloid deposition is a TiO2 seed layer, and its thickness is 50-500 nm.
[0020] In a third aspect, a flexible piezoelectric ultrasonic sensor is provided, comprising the PZT composite film described in the first aspect or the PZT composite film prepared according to the method described in the second aspect.
[0021] The beneficial effects of the present invention include:
[0022] (1) The PZT composite film provided by the present invention regulates the piezoelectric effect of the PZT film through the TiO2 seed layer, significantly improving the piezoelectric coefficient d33 of the PZT film, thereby making the prepared flexible piezoelectric ultrasonic sensor more sensitive to ultrasonic signals and more sensitive; and reducing the relative dielectric constant of the PZT film, which is beneficial to improving the intensity of the output signal of the flexible piezoelectric ultrasonic sensor.
[0023] (2) The addition of the TiO2 seed layer to the PZT composite film provided by the present invention not only improves the temperature stability, but also maintains the sensitivity of the flexible piezoelectric ultrasonic sensor to ultrasonic signals at high temperatures, thereby ensuring the reliability and effectiveness of the flexible piezoelectric ultrasonic sensor in high temperature environments. Therefore, it is more suitable for monitoring needs in high temperature environments such as complex power equipment.
[0024] (3) In the PZT composite film provided by the present invention, the addition of the TiO2 seed layer makes the PZT film have a denser and finer crystal structure, which is beneficial to improving the mechanical strength and thermal stability of the PZT composite film, thereby improving the stability and reliability of the flexible piezoelectric supersensor in complex environments.
[0025] (4) The flexible piezoelectric supersensor prepared by the PZT composite film provided by the present invention exhibits a wider frequency domain range in the lead breaking experiment and can detect more ultrasonic signal information.
[0026] (5) The preparation method of the PZT composite film provided by the present invention and the addition of the TiO2 seed layer have opened up a new path for the research and preparation of flexible piezoelectric ultrasonic sensors, which is helpful to promote the development of sensor technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] By reading the detailed description of the preferred specific embodiments below, various other advantages and benefits of the present invention will become clear to those of ordinary skill in the art. The drawings in the specification are only used for the purpose of illustrating the preferred embodiments and are not considered to be limitations of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, other drawings can also be obtained based on these drawings without creative work.
[0028] In the attached picture:
[0029] Figure 1 The SEM characterization image of the PZT composite film prepared in Example 1 is shown;
[0030] Figure 2 The SEM characterization image of the PZT composite film prepared in Comparative Example 1 is shown;
[0031] Figure 3The X-ray diffraction comparison diagram of the PZT composite film prepared in Example 1 and the PZT composite film prepared in Comparative Example 1 is shown;
[0032] Figure 4 The voltage-amplitude curve of the PZT composite film prepared in Example 1 is shown;
[0033] Figure 5 The voltage-amplitude curve of the PZT composite film prepared in Comparative Example 1 is shown;
[0034] Figure 6 A comparison diagram of relative dielectric constants of the PZT composite films prepared in Example 1 and Comparative Example 1 is shown;
[0035] Figure 7 The time domain signal diagram of the lead breaking experiment of preparing the PZT composite thin films obtained in Example 1 and Comparative Example 1 into sensors is shown;
[0036] Figure 8 The frequency domain signal diagram of the lead breaking experiment of preparing the PZT composite thin films obtained in Example 1 and Comparative Example 1 into sensors is shown;
[0037] Fig. 9 A temperature stability comparison chart of the flexible piezoelectric ultrasonic sensor made of Example 1, Comparative Example 1 and PVDF is shown. DETAILED DESCRIPTION
[0038] The following will refer to the attached Figures 1 to 9 Specific embodiments of the present invention are described in more detail. Although specific embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present invention and to fully convey the scope of the present invention to those skilled in the art.
[0039] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" is an open term, so it should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present invention, but the description is based on the general principles of the specification and is not intended to limit the scope of the present invention. The scope of protection of the present invention shall be determined by the attached claims.
[0040] In the description of the present invention, it should be noted that the terms "upper", "lower", "inner", "outer", "front", "rear", etc. indicate positions or positional relationships based on the working state of the present invention, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", "third", and "fourth" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.
[0041] To facilitate understanding of the embodiments of the present invention, further explanation will be given below by taking specific embodiments as examples in conjunction with the accompanying drawings, and each of the accompanying drawings does not constitute a limitation on the embodiments of the present invention.
[0042] In a first aspect, a PZT composite film is provided according to the present invention, and the piezoelectric effect of the PZT film is regulated by a TiO2 seed layer.
[0043] Among them, compared with the PZT thin film, the addition of the TiO2 seed layer introduces compression deformation, which makes the PZT composite film structure more compact and its mechanical properties better; at the same time, stress compression causes the upper and lower structures (PZT thin film layer and TiO2 seed layer) to be asymmetric, introducing spontaneous polarization phenomenon, making it easier to flip the polarization, thereby increasing d33; in addition, the TiO2 seed layer acts as a low dielectric constant layer, which reduces the overall dielectric constant, thereby improving the sensitivity of the prepared sensor.
[0044] Furthermore, the relative dielectric constant of the PZT composite film is 200~300, the piezoelectric coefficient d33 is 6.0pm / V, the piezoelectric response is 6-7 times higher than that of the film without adding the TiO2 seed layer, the mechanical strength is good, and it is not damaged after being bent multiple times at 0~90°. The stability of the PZT composite film remains unchanged in the temperature range of 0~200°C, that is, the relative dielectric constant and the piezoelectric coefficient remain unchanged.
[0045] In the present invention, the PZT composite film comprises from top to bottom: a PZT film layer, a TiO2 seed layer and a substrate.
[0046] Furthermore, the substrate can be a polymer substrate such as polyimide (PI), polyethylene terephthalate (PET), etc., or a metal platinum substrate such as copper foil, aluminum foil, etc., or an inorganic flexible substrate such as silicon nitride film, aluminum oxide film, etc., or a LNO / Mica substrate, preferably a LNO / Mica substrate.
[0047] Among them, in the LNO / Mica substrate, LNO (LaNiO3) has good conductivity, thermal stability and chemical stability, and Mica (mica), as a natural crystal, has good flexibility and heat resistance; the LNO / Mica substrate shows unique advantages in conductivity, structural stability, interface characteristics, adhesion, lattice matching, and thermal expansion coefficient matching. Using it as the substrate is currently the best choice for the present invention.
[0048] In the present invention, the thickness of the PZT thin film layer and the TiO2 seed layer is determined according to actual needs. Generally, the thickness of the PZT thin film layer is 500-2000nm, preferably 1000-1500nm, for example 1500nm; the thickness of the TiO2 seed layer is 50-500nm, preferably 100-250nm, for example 250nm.
[0049] Among them, the TiO2 seed layer is used as a growth layer. If it is too thin, the crystal structure is imperfect and cannot induce the orientation of the PZT thin film layer on it; if it is too thick, it is easy to break. PZT thin film is used as a piezoelectric layer. If it is too thin, the piezoelectric performance will be reduced. If it is too thick, the crystallization of the top layer is not ideal, the lead in the lower layer will volatilize seriously, and the performance will be reduced.
[0050] In a second aspect, according to the method for preparing the PZT composite thin film according to the first aspect provided by the present invention, the method comprises:
[0051] Step 1, depositing TiO2 precursor colloid on a substrate to obtain a TiO2 precursor film;
[0052] Step 2: depositing a PZT precursor sol on the TiO2 precursor film to obtain the PZT composite film.
[0053] Specifically:
[0054] Step 1: depositing TiO2 precursor colloid on a substrate to obtain a TiO2 precursor film.
[0055] According to a preferred embodiment, step 1 comprises the following steps:
[0056] Step 1-1, preparing TiO2 precursor colloid by sol-gel method;
[0057] Step 1-2, depositing TiO2 precursor colloid on a substrate to obtain a TiO2 precursor film.
[0058] In step 1-1, the sol-gel method includes: dissolving a titanium precursor by an organic solvent to prepare a TiO2 precursor colloid.
[0059] In the present invention, the titanium precursor is preferably tetrabutyl titanate and / or titanium n-propoxide, more preferably tetrabutyl titanate.
[0060] Among them, the sol-gel method is usually easy to operate and can be completed at room temperature. The titanium precursor mainly provides a titanium source, and tetrabutyl titanate helps to reduce the agglomeration of TiO2 particles during the sol-gel process, thereby obtaining a TiO2 precursor colloid with better dispersion.
[0061] In the present invention, the organic solvent is preferably selected from one or more of ethanol, ethylene glycol, and methyl ether, and more preferably ethanol.
[0062] Among them, all of the above organic solvents can dissolve titanium precursors, but ethanol is more prominent due to its low toxicity, easy removal, and low cost.
[0063] In the present invention, the mass ratio of the titanium precursor to the organic solvent is 1:(2-6), preferably 1:(3-6), for example 1:4.
[0064] The above mass ratio can completely dissolve the titanium precursor in the organic solvent and ensure that the TiO2 precursor colloid can be used in the homogenization process.
[0065] In the present invention, the dissolution time is 1 to 10 minutes, preferably 2 to 6 minutes, for example 5 minutes.
[0066] In the present invention, tetrabutyl titanate is used as a titanium precursor and ethanol is used as an organic solvent. At this time, tetrabutyl titanate reacts with ethanol to form colloidal particles with a three-dimensional network structure. These colloidal particles are TiO2 precursor colloids.
[0067] In step 1-2, the substrate can be a polymer substrate such as polyimide (PI), polyethylene terephthalate (PET), etc., or a metal platinum substrate such as copper foil, aluminum foil, etc., or an inorganic flexible substrate such as silicon nitride film, aluminum oxide film, etc., or a LNO / Mica substrate, preferably a LNO / Mica substrate.
[0068] In step 1-2, the deposition may be any one of atomic deposition, magnetron sputtering, and spin coating, preferably spin coating.
[0069] Among them, the equipment used for spin coating is relatively simple and easy to operate. The thickness of the deposited film can be precisely controlled by controlling the rotation parameters. For example, at 3000 rpm, the film thickness of the coating machine is about 50nm in one operation.
[0070] In step 1-2, after deposition, it is preferably further heat-treated to obtain a TiO2 precursor film. The heat treatment is used to dry the excess organic solvent and water in the TiO2 precursor colloid, and most importantly, to promote the formation and crystallization of titanium dioxide crystals.
[0071] Further, the heat treatment temperature is 500-700°C, preferably 600-700°C, for example 650°C; the heat treatment time is 1-3h, preferably 1.5-2.5h, for example 2h. Among them, the heat treatment temperature of 500-700°C is conducive to promoting crystal growth and crystallization, and improving the quality of the TiO2 seed layer. If the temperature is too high, the crystal may be too large or uneven, and if the temperature is too low, the rutile phase may be formed; 1-3h provides enough time for crystal growth and crystallization, while avoiding excessive crystal growth or unnecessary structural changes caused by too long a time. .
[0072] In the present invention, the thin film formed by the deposition of TiO2 precursor colloid on the TiO2 precursor thin film is the TiO2 seed layer.
[0073] Step 2: depositing a PZT precursor sol on the TiO2 precursor film to obtain the PZT composite film.
[0074] In step 2, the PZT precursor sol is prepared by a sol-gel method, which specifically includes:
[0075] Step 2-1, mixing a co-solvent and a catalyst to obtain a mixed sol;
[0076] Step 2-2, adding a lead compound, a zirconium compound and a titanium compound to the mixed sol to obtain the PZT precursor sol.
[0077] In step 2-1, the co-solvent is used to dissolve the lead compound, the zirconium compound and the titanium compound. The co-solvent is preferably 2-methoxyethanol. 2-methoxyethanol can not only dissolve the above compounds, but also help stabilize the sol and prevent the formation of precipitation.
[0078] In step 2-1, the catalyst is preferably acetic acid, which not only serves as a catalyst but also can better control the reaction rate.
[0079] In step 2-1, the mass ratio of the co-solvent to the catalyst is (2-8):1, preferably (4-5):1, for example 4:1.
[0080] Among them, if the ratio of co-solvent is too low, some compounds may not be fully dissolved and form precipitation; if the ratio is too high, although the solubility increases, it may have an adverse effect on subsequent reaction steps or product characteristics. Catalysts can accelerate the reaction rate, but the amount needs to be appropriate. If the ratio of the catalyst is too low, the catalytic effect is insufficient and the reaction rate is too slow; if the ratio is too high, the reaction rate may be too fast, making the reaction difficult to control, and may produce unwanted by-products or affect the structure of the final product. The mass ratio of the above co-solvent and catalyst is appropriate.
[0081] In step 2-1, the longer the mixing time of the co-solvent and the catalyst is, the more uniform the formed mixed sol is. Usually, the mixing time of the two is 1 to 3 hours, preferably 1 to 2 hours, for example 1 hour.
[0082] In step 2-2, the lead compound is selected from any one of lead acetate trihydrate, lead oxide, and lead acetate trihydrate, and is preferably lead acetate trihydrate [Pb(CH3COO)2·3H2O] having excellent solubility and stability.
[0083] In step 2-2, the zirconium compound is selected from any one of zirconium n-butoxide, zirconium oxide, and zirconium n-propoxide, and is preferably zirconium n-propoxide [Zr(OC3H9)4], which has strong solubility and controllability.
[0084] In step 2-2, the titanium compound is selected from any one of tetrabutyl titanate, titanium oxide, and titanium isopropionate, and is preferably tetrabutyl titanate [Ti(OC3H9)4] having excellent solubility and reactivity.
[0085] In step 2-2, the mass ratio of the lead compound, the zirconium compound and the titanium compound is 1:(0.3~0.6):(0.2~0.4), preferably 1:(0.5~0.6):(0.2~0.3), for example 1:0.56:0.3.
[0086] The lead compound is used in excess to compensate for the lead loss caused by the formation of the pyrochlore phase during the crystallization process.
[0087] According to a preferred embodiment, the lead compound, the zirconium compound and the titanium compound are sequentially added to the mixed sol.
[0088] Among them, the lead compound hydrolyzes and condenses in the mixed sol to form a basic framework, providing a stable reaction environment for the addition of zirconium compounds and titanium compounds; the subsequent addition of zirconium compounds is more conducive to adjusting the crystal phase of PZT; and the final addition of zirconium compounds helps to better control the gelation process, because titanium is more easily hydrolyzed and causes premature gelation of the sol, affecting the quality of the final product.
[0089] In the present invention, after the lead compound is added, the mixture is stirred for 10 to 20 minutes, such as 15 minutes, under water bath heating conditions, and then the heat source is removed and stirring is continued until the mixture reaches room temperature. The zirconium compound is added at room temperature and stirred for a second time for 5 to 10 minutes, such as 10 minutes, and then the titanium compound is added three times and stirred for 20 to 40 minutes, such as 30 minutes.
[0090] Furthermore, the water bath heating temperature is 50-90°C, preferably 60-80°C, for example 70°C.
[0091] Among them, heating conditions can accelerate the decomposition of lead compounds into lead ions and acetate ions during the hydrolysis process, thereby forming a metal oxide network structure; heating can also reduce the agglomeration of lead compounds. Within the above temperature range, the reaction rate can be better controlled and the occurrence of side reactions can be reduced.
[0092] In the present invention, after the stirring is completed, aging is performed for 18 to 48 hours, for example, 24 hours, to promote the formation of a gel network.
[0093] In step 2, the deposition may be any one of atomic deposition, magnetron sputtering, and spin coating, preferably spin coating.
[0094] Furthermore, the spin coating speed is 2000-4000 rps, preferably 2500-3500 rps, for example 3000 rps.
[0095] In step 2, 1-1.5 mL is dropped each time during spin coating, and then the PZT precursor sol is evenly spin coated at the above speed, followed by thermal processing according to the following procedure, and after the thermal processing is completed, the PZT precursor sol is dropped again for spin coating and thermal processing operations, that is, this operation is repeated until the desired PZT thin film layer thickness is reached. In fact, the thin film formed by depositing the PZT precursor sol is the PZT thin film layer.
[0096] Further, the thermal processing includes:
[0097] Stage I: heating from room temperature to 300~400℃ at a heating rate of 80~120℃ / min, and keeping warm for 1~3min;
[0098] Stage II: Continue heating from the first stage insulation temperature to 450~550℃ at a heating rate of 30~70℃ / min, and keep warm for 1~3min.
[0099] Among them, the PZT film is first pre-crystallized at a low temperature of 300~400℃ to reduce the internal stress, and then the temperature is raised to avoid the formation of the process pyrochlore phase.
[0100] In a further preferred embodiment, the thermal processing comprises:
[0101] Stage I: Heating from room temperature to 330~380℃ at a heating rate of 90~110℃ / min, and keeping warm for 1.5~2min;
[0102] Stage II: Continue heating from the first stage insulation temperature to 480~520℃ at a heating rate of 40~60℃ / min, and keep warm for 2~3min.
[0103] In a further preferred embodiment, the thermal processing comprises:
[0104] Stage I: Heating from room temperature to 350°C at a heating rate of 100°C / min, and keeping at this temperature for 2 minutes;
[0105] Stage II: Continue heating from the first stage holding temperature to 500°C at a heating rate of 50°C / min and keep warm for 2 minutes.
[0106] In step 2, after the last deposition is completed, the thermal processing before annealing preferably includes:
[0107] The first stage: heating from room temperature to 300~400℃ at a heating rate of 80~120℃ / min, and keeping warm for 1~3min;
[0108] The second stage: continue to heat up from the first stage holding temperature to 450~550℃ at a heating rate of 30~70℃ / min, and keep warm for 3~8min;
[0109] The third stage: continue to heat up from the second stage insulation temperature to 600~700℃ at a heating rate of 30~70℃ / min, keep it at that temperature for 8~15min, and then cool it down naturally.
[0110] The generation of the pyrochlore phase is avoided by heating in stages, and the internal stress of the TiO2 seed layer and the PZT thin film layer is optimized by the thermal processing before the annealing.
[0111] In a further preferred embodiment, the thermal processing before annealing preferably includes:
[0112] The first stage: heating from room temperature to 330~380℃ at a heating rate of 90~110℃ / min, and keeping warm for 1.5~2min;
[0113] The second stage: continue to heat up from the first stage holding temperature to 480~520℃ at a heating rate of 40~60℃ / min, and keep warm for 4~6min;
[0114] The third stage: continue to heat up from the second stage insulation temperature to 620~660℃ at a heating rate of 40~60℃ / min, keep it for 9~12min, and then cool it down naturally.
[0115] In a further preferred embodiment, the thermal processing before annealing preferably includes:
[0116] The first stage: heating from room temperature to 350°C at a heating rate of 100°C / min, and keeping the temperature for 2 minutes;
[0117] The second stage: the temperature is raised from the first stage holding temperature to 500°C at a heating rate of 50°C / min and kept at this temperature for 5 minutes;
[0118] The third stage: continue to heat up from the second stage holding temperature to 650°C at a heating rate of 50°C / min, keep warm for 10 minutes, and then cool naturally.
[0119] In the present invention, the normal temperature is room temperature.
[0120] In a third aspect, a flexible piezoelectric ultrasonic sensor is provided, which adopts the PZT composite film described in the first aspect or the PZT composite film produced by the method described in the second aspect.
[0121] The present invention is further described below through specific examples, but these examples are merely exemplary and do not constitute any limitation to the scope of protection of the present invention.
[0122] Example 1
[0123] (1) 5 g of tetrabutyl titanate was dissolved in 20 g of anhydrous ethanol for 5 min to obtain a TiO2 precursor colloid; then, 1 g of the TiO2 precursor colloid was spin-coated on the LNO / Mica substrate at a speed of 3000 r / min, and then heat-treated at 650°C for 2 h to obtain a TiO2 precursor film, wherein the thickness of the TiO2 seed layer deposited on the TiO2 precursor film was 250 nm;
[0124] (2) Acetic acid and 2-methoxyethanol were mixed in a mass ratio of 1:4, and the two were stirred for 1 hour to obtain a mixed sol; 4.332 g of lead acetate was added to the mixed sol, heated in a water bath at 70°C and stirred for 15 minutes at a time, then the heat source was removed and continued to stir until the temperature reached room temperature, 2.4334 g of zirconium n-propoxide was added at room temperature, stirred for 10 minutes twice, and then 1.3200 g of tetrabutyl titanate was added and stirred for 30 minutes three times. After the above stirring was completed, the mixture was aged for 24 hours to obtain a PZT precursor sol;
[0125] 20 drops (1.5 mL) of PZT precursor sol were dropped onto the TiO2 precursor film prepared in step (1), and the PZT precursor sol was evenly spin-coated at 3000 rps, followed by thermal processing according to the following procedure:
[0126] Stage I: Heating from room temperature to 350°C at a heating rate of 100°C / min, and keeping at this temperature for 2 minutes;
[0127] Stage II: Continue heating from the first stage holding temperature to 500°C at a heating rate of 50°C / min and keep warm for 2 minutes;
[0128] After the thermal processing is completed, the PZT precursor sol is dripped again to perform the above spin coating and thermal processing operations until the required PZT thin film layer thickness is reached. The last thermal processing, that is, the thermal processing before annealing, is performed according to the following procedures:
[0129] The first stage: heating from room temperature to 350°C at a heating rate of 100°C / min, and keeping the temperature for 2 minutes;
[0130] The second stage: the temperature is raised from the first stage holding temperature to 500°C at a heating rate of 50°C / min and kept at this temperature for 5 minutes;
[0131] The third stage: the temperature is raised from the second stage holding temperature to 650°C at a heating rate of 50°C / min, kept at that temperature for 10 minutes, and then cooled naturally;
[0132] After the above operations are completed, a PZT composite thin film is obtained, wherein the thickness of the PZT thin film layer is 1500 nm.
[0133] Example 2
[0134] (1) 5 g of tetrabutyl titanate was dissolved in 30 g of anhydrous ethanol for 5 min to obtain a TiO2 precursor colloid; then, 1 g of the TiO2 precursor colloid was spin-coated on the LNO / Mica substrate at a speed of 2000 r / min, and then heat-treated at 650°C for 2 h to obtain a TiO2 precursor film, wherein the thickness of the TiO2 seed layer deposited on the TiO2 precursor film was 250 nm;
[0135] (2) Acetic acid and 2-methoxyethanol were mixed in a mass ratio of 1:4, and the two were stirred for 1 hour to obtain a mixed sol; 4.332 g of lead acetate was added to the mixed sol, heated in a water bath at 70°C and stirred for 15 minutes at a time, then the heat source was removed and continued to stir until the temperature reached room temperature, 2.4334 g of zirconium n-propoxide was added at room temperature, stirred for 10 minutes twice, and then 1.3200 g of tetrabutyl titanate was added and stirred for 30 minutes three times. After the above stirring was completed, the mixture was aged for 24 hours to obtain a PZT precursor sol;
[0136] 20 drops (1.5 mL) of PZT precursor sol were dropped onto the TiO2 precursor film prepared in step (1), and the PZT precursor sol was evenly spin-coated at 3000 rps, followed by thermal processing according to the following procedure:
[0137] Stage I: Heating from room temperature to 350°C at a heating rate of 100°C / min, and keeping at this temperature for 2 minutes;
[0138] Stage II: Continue heating from the first stage holding temperature to 500°C at a heating rate of 50°C / min and keep warm for 2 minutes;
[0139] After the thermal processing is completed, the PZT precursor sol is dripped again to perform the above spin coating and thermal processing operations until the required PZT thin film layer thickness is reached. The last thermal processing, that is, the thermal processing before annealing, is performed according to the following procedures:
[0140] The first stage: heating from room temperature to 350°C at a heating rate of 100°C / min, and keeping the temperature for 2 minutes;
[0141] The second stage: the temperature is raised from the first stage holding temperature to 500°C at a heating rate of 50°C / min and kept at this temperature for 5 minutes;
[0142] The third stage: the temperature is raised from the second stage holding temperature to 650°C at a heating rate of 50°C / min, kept at that temperature for 10 minutes, and then cooled naturally;
[0143] After the above operations are completed, a PZT composite thin film is obtained, wherein the thickness of the PZT thin film layer is 1500 nm.
[0144] Comparative Example 1
[0145] The PZT composite thin film was prepared in a similar manner to Example 1, except that there was no TiO2 seed layer. The specific steps were as follows:
[0146] Acetic acid and 2-methoxyethanol were mixed in a mass ratio of 1:4, and the two were stirred for 1 hour to obtain a mixed sol; 4.332g of lead acetate was added to the mixed sol, heated in a water bath at 70°C and stirred for 15 minutes at a time, then the heat source was removed and continued to stir until the temperature reached room temperature, 2.4334g of zirconium n-propoxide was added at room temperature, stirred for 10 minutes twice, and then 1.3200g of tetrabutyl titanate was added and stirred for 30 minutes three times. After the above stirring was completed, the mixture was aged for 24 hours to obtain a PZT precursor sol;
[0147] 20 drops (1.5 mL) of PZT precursor sol were dropped on the LNO / Mica substrate, and the PZT precursor sol was evenly spin-coated at 3000 rps, followed by thermal processing according to the following procedure:
[0148] Stage I: Heating from room temperature to 350°C at a heating rate of 100°C / min, and keeping at this temperature for 2 minutes;
[0149] Stage II: Continue heating from the first stage holding temperature to 500°C at a heating rate of 50°C / min and keep warm for 2 minutes;
[0150] After the thermal processing is completed, the PZT precursor sol is dripped again to perform the above spin coating and thermal processing operations until the required PZT thin film layer thickness is reached. The last thermal processing, that is, the thermal processing before annealing, is performed according to the following procedures:
[0151] The first stage: heating from room temperature to 350°C at a heating rate of 100°C / min, and keeping the temperature for 2 minutes;
[0152] The second stage: the temperature is raised from the first stage holding temperature to 500°C at a heating rate of 50°C / min and kept at this temperature for 5 minutes;
[0153] The third stage: the temperature is raised from the second stage holding temperature to 650°C at a heating rate of 50°C / min, kept at that temperature for 10 minutes, and then cooled naturally;
[0154] After the above operations are completed, a PZT composite thin film is obtained, wherein the thickness of the PZT thin film layer is 1500 nm.
[0155] Figure 1 The SEM characterization image of the PZT composite film prepared in Example 1 is shown. Figure 2 The SEM characterization image of the PZT composite film prepared in Comparative Example 1 shows that the PZT composite film prepared in Example 1 has finer grains and is more compact, which is the reason for its stronger mechanical properties; at the same time, the growth of columnar crystals causes its piezoelectric properties to be significantly stronger than that of Comparative Example 1.
[0156] Figure 3 The X-ray diffraction (XRD) comparison diagram of the PZT composite film prepared in Example 1 and the PZT composite film prepared in Comparative Example 1 is shown, and it can be found that the PZT composite films prepared in Example 1 and Comparative Example 1 have good crystallization quality and no impurity phase is generated; but the diffraction peaks of the PZT composite film prepared in Example 1 are all shifted to low angles, and the piezoelectric coefficient d33 reaches 6.0pm / V, indicating that the addition of the TiO2 seed layer introduces compressive stress, so that the piezoelectric performance and mechanical strength of Example 1 are much higher than those of Comparative Example 1.
[0157] The PZT composite films prepared in Example 1 and Comparative Example 1 were tested for piezoelectric response under atomic force microscopy. Figure 4 The voltage-amplitude curve of the PZT composite film prepared in Example 1 is shown. Figure 5The voltage-amplitude curve of the PZT composite film prepared in Comparative Example 1 is shown. It can be seen that the response of the PZT composite film prepared in Example 1 reaches about 6nm, which is significantly higher than the 1.2nm of the PZT composite film prepared in Comparative Example 1, and is about 5 times that of the PZT composite film prepared in Example 1. This indicates that the PZT composite film prepared in Example 1 can better convert force signals into electrical signals and is more suitable for preparing high-performance flexible piezoelectric ultrasonic sensors.
[0158] Figure 6 A comparison chart of the relative dielectric constants of the PZT composite films prepared in Example 1 and Comparative Example 1 is shown. It can be seen that the relative dielectric constant of the PZT composite film prepared in Example 1 is lower, which indicates that Example 1 has better sensitivity response and is more suitable for making high-performance flexible piezoelectric ultrasonic sensors.
[0159] The PZT composite films prepared in Example 1 and Comparative Example 1 were respectively prepared into sensors according to the following steps: the PZT composite films prepared in Example 1 and Comparative Example 1 were respectively placed in the positive and negative electrodes and led out through wires, and then connected to the BNC copper axis, the PZT composite film and the wires were clamped and bonded together by a PEI flexible board, and then the periphery was wrapped with copper foil to form an electromagnetic shield. Afterwards, the above two sensors were subjected to a lead breaking experiment according to the following method: the two sensors were respectively placed on a polyethylene sheet with a radius of 30 cm and a thickness of 10 cm, so that they were kept 15 cm away from the center of the circle, and silicone grease was used to ensure that the sensor and the sheet fit tightly. Subsequently, at the center of the sheet, a 1 cm long automatic pencil lead was pressed at a 45-degree angle to break. At this time, the two sensors will synchronously collect the signal generated by the pencil lead break.
[0160] Figure 7 The time domain signal diagrams of the lead-breaking experiment of the PZT composite films prepared in Example 1 and Comparative Example 1 are shown respectively. It can be seen that the response ability of the sensor prepared in Example 1 to the same lead-breaking signal is 6-7 times that of Comparative Example 1, indicating that Example 1 has better sensitivity response and is more suitable for making high-performance flexible piezoelectric ultrasonic sensors.
[0161] Figure 8 The frequency domain signal diagrams of the lead-breaking experiment of the PZT composite thin films prepared in Example 1 and Comparative Example 1 are shown. It can be seen that the sensitivity of the thin film sensor prepared in Example 1 to ultrasonic signals of different frequency bands of the same lead-breaking signal is 6-7 times that of Comparative Example 1, indicating that Example 1 has a better sensitivity response and is more suitable for making high-performance flexible piezoelectric ultrasonic sensors. Figure 7 and Figure 8 It can be seen that the flexible piezoelectric ultrasonic sensor made of the PZT composite film in Example 1 is more sensitive to ultrasonic signals and can monitor a wider frequency domain range of ultrasonic signals.
[0162] The flexible piezoelectric ultrasonic sensor made of Example 1, Comparative Example 1 and PVDF (the flexible piezoelectric ultrasonic sensor made of PVDF) Fig. 9 The PVDF was placed in an oven and heated step by step, starting from 25°C and increasing the temperature by 20°C to 260°C. The temperature was kept at each temperature for 20 minutes, and then the lead breaking experiment was carried out. Fig. 9 A temperature stability comparison chart is shown, from which it can be seen that the temperature stability exhibited by the flexible piezoelectric ultrasonic sensor made of the PZT composite film in Example 1 during the heating process is far superior to that of the other two flexible piezoelectric ultrasonic sensors, indicating that the addition of the TiO2 seed layer can significantly improve the temperature stability of the PZT flexible piezoelectric ultrasonic sensor.
[0163] In summary, it is obvious that by regulating the performance of the PZT film through the TiO2 seed layer, the obtained PZT composite film has a higher piezoelectric coefficient and a lower dielectric constant, can withstand higher temperatures, and the prepared flexible piezoelectric ultrasonic sensor has higher sensitivity and thermal stability.
[0164] The present invention is described in detail above in combination with preferred embodiments and exemplary examples. However, it should be noted that these specific embodiments are only illustrative explanations of the present invention and do not constitute any limitation on the protection scope of the present invention. Without exceeding the spirit and protection scope of the present invention, various improvements, equivalent substitutions or modifications may be made to the technical content of the present invention and its embodiments, which all fall within the protection scope of the present invention. The protection scope of the present invention shall be subject to the attached claims.
Claims
1. A PZT composite thin film, characterized in that: The piezoelectric effect of PZT thin film is regulated by TiO2 seed layer.
2. The PZT composite thin film according to claim 1, characterized in that: Preferably, the relative dielectric constant of the PZT composite film is 200-300.
3. The PZT composite thin film according to claim 1, characterized in that: The PZT composite film comprises from top to bottom: a PZT film layer, a TiO2 seed layer and a substrate.
4. The PZT composite thin film according to claim 3, characterized in that: The thickness of the TiO2 seed layer is 50-500 nm.
5. The PZT composite thin film according to claim 3, characterized in that: The thickness of the PZT thin film layer is 500-2000 nm.
6. The PZT composite thin film according to claim 3, characterized in that: The substrate is a polymer substrate, a metal platinum substrate or a LNO / Mica substrate.
7. A method for preparing the PZT composite thin film according to any one of claims 1 to 6, characterized in that: The method comprises: Step 1, depositing TiO2 precursor colloid on a substrate to obtain a TiO2 precursor film; Step 2: depositing a PZT precursor sol on the TiO2 precursor film to obtain the PZT composite film.
8. The method according to claim 7, characterized in that In step 1, the TiO2 precursor colloid is prepared by a sol-gel method.
9. The method according to claim 7, characterized in that: In step 1, the thin film formed by the TiO2 precursor colloid deposition is a TiO2 seed layer, and its thickness is 50-500 nm.
10. A flexible piezoelectric ultrasonic sensor, characterized in that: The invention comprises the PZT composite film according to any one of claims 1 to 6 or the PZT composite film prepared by the method according to any one of claims 7 to 9.
Citation Information
Patent Citations
Method for manufacturing multilayer film, and multilayer film
CN106062239A
Preparation method of (100) preferred orientation PMN-PZT / PZT heterostructure film
CN111081864A
Flexible piezoelectric sensor, preparation method thereof and pulse wave detection method
CN116782743A
Method for regulating and controlling performance of flexible PZT film by using substrate electrode
CN117881266A
Seed layer formation element
JP2001308290A